2018
DOI: 10.12816/0044770
|View full text |Cite
|
Sign up to set email alerts
|

Anemia : Its Prevalence, Causes and Management

Abstract: Background: Nutritional anemia or anemia due to dietary causes is the most common form, yet the easiest to manage compared to other forms of anemia. Some of the most common nutritional deficiencies are iron, cobalamin, folate, and also other elements like copper. Anemia due to diet is mostly asymptomatic in the initial phase until the stores are depleted, which can take a few months to several years, depending upon the cause. Methodology: We conducted this review using a comprehensive search of MEDLINE, PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…This was in agreement with Sharourou et al, 2018 who found that the most important cause of anemia was iron deficiency anaemia [8] . Also, Al Hassan., 2015 found that iron deficiency anaemia was the most common type of anaemia represented 81% with mean hemoglobin concentration for the study sample was 9.8 ± 7 g/dl [9] .…”
Section: Discussionsupporting
confidence: 92%
“…This was in agreement with Sharourou et al, 2018 who found that the most important cause of anemia was iron deficiency anaemia [8] . Also, Al Hassan., 2015 found that iron deficiency anaemia was the most common type of anaemia represented 81% with mean hemoglobin concentration for the study sample was 9.8 ± 7 g/dl [9] .…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have associated certain nutritional insufficiencies with this disease. Iron, vitamin B12, folic acid, vitamin A, and vitamin C are some nutrients that have been linked to its development ( 6 , 11 – 16 ). The association between nutrient intake deficiencies and other health and cognitive development problems among schoolchildren has been investigated by several studies, indicating a strong correlation between nutrition and the health of children.…”
Section: Introductionmentioning
confidence: 99%
“…Research revealed that about 27% of adolescents living in the least developed countries suffer from anaemia mostly related to iron (Sharourou et al, 2018). Ghana Micronutrients Survey (2017) estimated the prevalence of iron deficiency anaemia to be 21.7% among women of reproductive age (15–49 years old).…”
Section: Introductionmentioning
confidence: 99%